Evaluation of Functional Results of Type C Distal Humeral Fractures by Fixation with Precontoured Locking Parallel Plates (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the functional results of type C fractures (AO Classification) of the distal humerus in adults by the parallel platting system Methods: This Prospective Study was conducted from Sep 2012 to April 2015. A total of thirty two patients were included in the study who presented in Accident and Emergency department after trauma around elbow joint with type C distal humerus fractures. They were treated by parallel plates along both sides of distal humerus at 180o. Patients were followed for 2 weeks, 1 month, 2months, 3 months, 6 months and 1 year. They were evaluated for union, movements and functional outcome at elbow joint according to the Mayo Scoring system and also for any complication and disability by Disability of Arm, Shoulder and Hand (DASH) score. Results: The functional results were evaluated in terms of Mayo Elbow Performance score (MEPS) and Disability of Arm, Shoulder and Hand (DASH) score., the mean MEPS after one year was 89±3.5 and DASH score was 25±3.7. The range of movements improved within first 3 months. Mean elbow flexion was 115±10° and extension was 10±5. Conclusion: Parallel plating system provide better stability in all the distal humeral intraarticular fractures especially in the old age patients when used with locking screws. Early range of movements are started leading to better results.
Keywords: Parallel Platting, Humeral Fractures